2018
DOI: 10.1002/jcp.26599
|View full text |Cite
|
Sign up to set email alerts
|

CD69 partially inhibits apoptosis and erythroid differentiation via CD24, and their knockdown increase imatinib sensitivity in BCR‐ABL‐positive cells

Abstract: Chronic myeloid leukemia (CML) is caused by a constitutively active BCR-ABL tyrosine kinase. Tyrosine kinase inhibitors (TKIs) imatinib and its derivatives represent a breakthrough for CML therapy, but the use of TKI alone is ineffective for many CML patients. CD69, an early activation marker of lymphocytes, participates in immune and inflammatory responses. Previous studies revealed that BCR-ABL upregulates CD69 expression; however, the role of CD69 in CML cells is unknown. Here, we demonstrate that BCR-ABL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…NF-κB regulates the transcription of many pro-inflammatory and pro-survival genes. We found nine upregulated pro-survival genes in MIS-C compared to KD, including S100A3 [51], TNFRSF4 [52], BIRC3 [53], WWC1 [54], VNN1 [55], CD69 [56], LTB [57], TRAF1 [58], and ANO9 [59]. We also found that an independent pro-apoptotic gene, IGFBP5 [60], was downregulated in MIS-C. Taken together, these findings suggest that ECs in MIS-C have a more pro-survival phenotype compared to KD.…”
Section: Discussionsupporting
confidence: 57%
“…NF-κB regulates the transcription of many pro-inflammatory and pro-survival genes. We found nine upregulated pro-survival genes in MIS-C compared to KD, including S100A3 [51], TNFRSF4 [52], BIRC3 [53], WWC1 [54], VNN1 [55], CD69 [56], LTB [57], TRAF1 [58], and ANO9 [59]. We also found that an independent pro-apoptotic gene, IGFBP5 [60], was downregulated in MIS-C. Taken together, these findings suggest that ECs in MIS-C have a more pro-survival phenotype compared to KD.…”
Section: Discussionsupporting
confidence: 57%
“…CD69, a member of the calcium-dependent lectin superfamily of type II transmembrane receptors, was reported as the marker for BCR-ABL activity in chronic myeloid leukemia [67]. In addition, CD69 was found to inhibit the apoptosis and differentiation in K562 cells [68]. RT-Q-PCR in Figure 6b validated that 8-OHD (50 and 100 µM) inhibits CD69 mRNA expression after 48 h treatment.…”
Section: Analysis Of 8-ohd-modulated Gene Expressionmentioning
confidence: 70%
“…S5 A ). Among those genes down-regulated were several with known roles in erythroid differentiation, including vimentin ( Vim ) required for enucleation ( Xue et al, 1997 ) and the enzyme coproporphyrinogen III oxidase ( Cpox ) required for Hgb synthesis ( Taketani et al, 2001 ), whereas CD69, which inhibits erythroid differentiation ( Huang et al, 2018 ), was up-regulated ( Fig. 6 B and Fig.…”
Section: Resultsmentioning
confidence: 99%